2013
DOI: 10.1039/c3ob40106e
|View full text |Cite
|
Sign up to set email alerts
|

Caged retinoids as photoinducible activators: implications for cell differentiation and neurite outgrowth

Abstract: Aiming to control neurite formation and navigate the axonal growth by an extrinsic guidance, we report on the design, synthesis and biological evaluation of caged retinoids. Agonists of RARβ have been temporarily blocked either by the [(α-methyl-2-nitropiperonyl)oxy]carbonyl (MeNPOC) group or by immobilization using nitrocatechol linkers on TiO2 particles. Release on demand has been achieved by release under UV irradiation, leading to the biologically active compounds, which have been shown to induce neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Previous work has shown that activation of RAR-β stimulates neurite growth (1315). Because the process of constant cytoskeletal rearrangement in the elongating axon requires a continuous supply of energy in areas distal from the cell body (31), proper mitochondrial distribution is required for axonal regeneration (3), and axonal injury increases mitochondrial movement (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that activation of RAR-β stimulates neurite growth (1315). Because the process of constant cytoskeletal rearrangement in the elongating axon requires a continuous supply of energy in areas distal from the cell body (31), proper mitochondrial distribution is required for axonal regeneration (3), and axonal injury increases mitochondrial movement (4).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown, in refs. [13][14][15], that retinoic acid induces axonal and neurite outgrowth by activating the retinoic acid receptor (RAR)-b, but the role of retinoids in mitochondrial mobilization or recruitment is yet to be described. Furthermore, considering the essential role of mitochondria in neurite elongation, and taking into account the role of hypoxia signaling in peripheral neurite regeneration, it is pertinent to investigate whether retinoic acid promotes neurite elongation in the CNS by acting via this signaling pathway.…”
mentioning
confidence: 99%
“…Recently Hoecker et al. deposited acyl homoserine lactone and a nitrodopamine onto biocompatible TiO 2 beads by an operationally simple dip‐and‐rinse procedure, and showed that these beads are capable of inducing quorum sensing (QS) 128a. This hybrid system expands the catechol surface‐modification platform and provides a straightforward method for the preparation of coated surfaces in medical devices able to interrupt the QS signaling pathway in a wide range of different bacterial strains 130.…”
Section: Catecholsmentioning
confidence: 99%
“…However, the application of NGF as a drug is limited because it cannot cross the blood brain barrier (BBB). Thus, finding small molecules that have neurotrophic properties similar to those of NGF (NGF mimics) [68] and can cross the BBB is of great importance. Natural products are a great source of compounds for medical uses.…”
Section: Introductionmentioning
confidence: 99%